Kebijakan Perpajakan dan Peran Model Triple Helix berpengaruh dalam Meningkatkan Kepatuhan Pajak Pada UMKM Kecamatan Ciawi - Fahmi, Tubagus Ahmad Alfi Fahmi; Bagas Arya Agustyo; Roby Awaludin; Arifin Billah; Iin Rosini (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study was conducted to assess the influence of tax policy and the role of the Triple Helix model on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Ciawi District. The persistent issue of low tax compliance within the MSME sector serves as the primary rationale for this investigation. A quantitative approach was applied, utilizing multiple linear regression analysis. Primary data were collected through questionnaires distributed to 95 MSME respondents, followed by instrument testing through validity, reliability, normality, and multicollinearity tests, as well as inferential statistical analysis using t-tests and F-tests. The findings indicate that tax policy exerts a positive and significant effect on MSME tax compliance, as evidenced by a regression coefficient of 0.271 with a significance level of 0.000. Furthermore, the role of the Triple Helix model—comprising collaborative engagement between government, private sector, and academic institutions—also demonstrates a positive and significant impact on tax compliance, with a regression coefficient of 0.794 at the same significance threshold. Simultaneously, these two variables collectively explain 76.4% of the variation in MSME tax compliance. These results highlight the importance of optimizing adaptive tax policies and strengthening cross-sector collaboration within the Triple Helix framework as strategic measures to enhance MSME tax compliance. The strategic implications suggest the need for tax policy reformulation and the development of sustainable collaborative models to promote higher tax compliance in the MSME sector